Ketahanan Tiga Varietas Unggul Baru (Vub) Pisang Terhadap Beberapa Vegetative Compatibility Groups Fusarium oxysporum f. sp. cubense - no, Jumjunidang; Riska; Yanda, Resta Patma; Purnama, Titin; Sutanto, Agus; Hermanto, Catur (Jurnal Fitopatologi Indonesia, 2021)
Resistance of Three Superior New Banana Varieties on Several Vegetative Compatibility Groups Fusarium oxysporum f. sp. cubense Indonesian Tropical Fruits Research Institute (ITFRI) has released three New Superior Varieties of bananas. In supporting the successful of new banana variety development is necessary to know information of the response of resistance variety to Fusarium oxysporum f. sp. cubense (Foc) in several VCGs. The aim of this research was to determine the three bananas new superior varieties resistance response against VCGs of Foc in screen house test. The experiment was conducted in plant protection laboratory and screen house of ITFRI, from September 2016 to December 2017. The design used was randomized block, 21 treatments and 3 replications; each treatment consisted of 10 plants. The treaments were Ketan 01 (AA), Kepok Tanjung (ABB/BBB) and Raja Kinalun (ABB), each was inoculated with 7 VCGs of Foc (VCG 0120/15, 0123, 0124/5, 0126, 01218, 01213/16 dan 01219). The results revealed that the three new superior banana varieties showed varying resistance responses (highly resistant-highly susceptible) to VCGs of Foc isolates in race 1 and race 4. Resistance of three new superior quality varieties of bananas was not associated with a group of pathogenic Foc in race, but was influenced by compatibility each of the VCGs of Foc isolates and banana variety. Kepok Tanjung (ABB/BBB) variety was susceptible and highly susceptible to all VCGs of Foc isolates tested, Ketan 01 (AA) variety was resistant to all VCGs of Foc isolates tested, except Foc VCGs 0124/5 (race 1) and VCGs 01213/16 (Tropical race 4). Raja Kinalun (ABB) variety was resistant and highly resistant to all used fungal isolates, except Foc VCGs 0124/5 (race 1), the response of it was highly susceptible. This information is expected to support the development of new superior quality varieties of bananas in Indonesia.